Development and study of electrochemical procedures and of modified electrodes for the determination of trace metallic species in solution - Chen, Bing. (2009)
This thesis describes the development and study of electroanalytical procedures for the determination of trace metallic species in solution. Two major studies are included. In the first study, a square wave stripping voltammetric procedure, utilizing a thin film mercury electrode, was developed and optimized. The procedure was suitable for the determination of Cd, Pb and Cu at the |ig/L concentration level in natural water. The second study included the construction and characterization of graphite paste electrodes which were modified with zeolite molecular sieves. In conjunction with a medium exchange procedure, electrode sensitivity to traces of Cu, Cd and Zn was achieved. Furthermore, the interference effects from Co(II), Pb(II), Ni(II), Al(III), Cd(II), Cu(II), Ag(I) and Hg(II) on the Zn signals were studied. Most notably it was observed that the interference was stronger for species, which had the higher coordination number in solution. This suggests that electrode sensitivity and selectivity were partially governed by the coordination numbers of the metallic species.